Fracture Characteristics and Anisotropic Strength Criterion of Bedded Sandstone - Zhang, Liang; Niu, Fujun; Liu, Minghao; Ju, Xin; Wang, Zhiwei; Wang, Jinchang; Dong, Tianchun (Frontiers in Earth Science, 2022)
Bedded sandstone belongs to sedimentary rock, which has obvious layered characteristics and is a typical bedded rock, which exhibits anisotropic mechanical behavior due to the different bedding orientations. Therefore, the strength anisotropy of bedded sandstone depends on the bedding orientation. In this study, the fracture characteristics and strength criterion of bedded sandstone are studied by performing triaxial compression tests on rock specimens with different bedding dip angles under different confining pressure conditions. The test results show that the failure mode and strength of the bedded sandstone are related to the bedding dip angle and have obvious anisotropy. The experimental data was broadly in line with the Jaeger's surface of weakness (JPW) model. However, considering the difference in the strength of sandstone specimens with horizontal bedding dip (β = 0°) and vertical bedding dip (β = 90°), an improved JPW model is proposed to distinguish the strength criteria for the above differences. In addition to this, the nonlinear relationship between confining pressure and rock compressive strength is considered and improved in the model to adapt the model to the prediction of the strength behavior of bedded rocks.